Modificação covalente de peptideos antimicrobianos e anticancerigenos para a melhoria de suas propriedades farmacológicas - Morales Vicente, Fidel Ernesto (2019)
Following the information obtained by a rational design study, cyclic and dimeric helical stabilized analogues of the peptide Cm-p5 were synthetized. The cyclic monomer showed an increased activity in vitro against Candida albicans and Candida parapsilosis, compared to Cm-p5. Initially, fourteen mutants of Cm-p5 were synthesized following a rational design to improve the antifungal activity and pharmacological properties. Antimicrobial testing showed that the activity was lost in every of these fourteen analogues, suggesting as a main conclusion, that a Glu-His salt bridge could stabilize Cm-p5 helical conformation during the interaction with the plasma membrane. A derivative, obtained by substitution of Glu and His for Cys, was synthesized and oxidized with the generation of a cyclic monomer with improved antifungal activity. In addition, two dimers were generated during the oxidation procedure, a parallel and anti-parallel one. The dimers showed a helical secondary structure in water, whereas the cyclic monomer only showed this conformation in SDS. In addition, the antiparallel dimer showed a moderate activity against Pseudomonas aeruginosa and a significant activity against Listeria monocytogenes. Nor the cyclic monomer nor the dimers were toxi c against macrophages or THP-1 human cells. Continuing with the covalent modifications of the Cm-p5 structure, in chapter 2 is described the design, synthesis and characterization of 15 lipidated and cyclo-lipidated analogues of Cmp5. Previous studies showed that N-lipidation of Cm-p5 by Ugi-4CR increase notably the antifungal activity. Our initial biological test showed that lipidation with decanoic acid did not display any effect inthe activity of Cm-p5, while pentadecanoic acid decreased it. These results are not in accord with the increased activity in case of the Ugi lipidated analogue. The Ugi-4CRdo not only introduces a lipid chain, also produce N-substitution that can alter the conformational behavior of the lipid chain. To determine the influence of N-substitution, three analogues containing Ala, Gly or Pro between the lipid chain and the normal sequence of Cmp5 was synthetized. Gly and Pro are implied in several conformational changes in proteins or peptides.Gly possesses high flexibility while Pro is the only N-alkylated aminoacid and participate in loop or rigid structure formation. In addition, following the expected increase of activity by disulfide bridge formation, similar variants possessing Ala (introduced as a comparison), Gly or Pro between adodecyl chain and cyclic/dimeric CysCysCm-p5 were XVII prepared. Finally, lipidationby Ugi-4CR with n-dodecylisonitrile and subsequent cyclization between Cys produce cyclic and dimeric versions of Ugi lipidated cyclopeptides. All compoundsare under biological evaluation thatwill permit to gainconclusion about the structural motif needed to produce the more antifungal cyclic and lipidated analogue of Cm-p5. In chapter 3, we used the combination of solid phase and liquid phase methods for the synthesis of the anticancer drug, carfilzomib (CFZ). The convergent route comprises the tetrapeptide construction in solid phase followed by coupling with the previously prepared Leu-epoxide. Side effects of CFZ include the heart failure and shortness of breath so that the development of bioconjugation for targeted delivery is desired. With this aim, we prepared a traceless carbonylacrylic-Val-Cit-PAB linker as an alcohol in solid phase using the special DHP resin in high yield. This alcohol linker was tosylated and iodinated with the aim of improve the yields of the substitution reaction with CFZ (substitution of tosylate need heating). The pH (low) insertion peptides (pHLIPs) target acidity at the surfaces of cancer cells and show utility in a wide range of applications, including tumor imaging and intracellular delivery of therapeutic agents. We pretend to merge the capacity of tumor cell selectivity of pHLIP peptide with the traceless, stability and selective delivery of the new carbonylacrylic linker. Finally, the bioconjugation of CFZ to pHLIP peptide through the carbonylacrylic-Val-Cit-PAB linker, for the traceless release and targeted delivery to tumors could significantly improve the effectiveness of this drug in cancer treatment.